PENERAPAN KOMUNIKASI ISLAM PADA LINGKUNGAN PONDOK PESANTREN SALAF DALAM METODE PEMBELAJARAN KITAB KUNING - Siti Rohmah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to explore the application of Islamic communication in a salaf pesantren environment, especially in the method of learning kitab kuning. Islamic communication here is understood as a form of interaction based on Islamic values such as honesty, politeness, and respect. Salaf Islamic boarding schools were chosen as the object of research because they are known for their traditional learning methods that are deep and thick with Islamic nuances. The methodology used in this research is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results showed that Islamic communication plays an important role in the process of learning the yellowclassical books. Islamic communication values are applied through various activities, such as recitation, group discussions, and daily interactions between santri and ustadz. The application of Islamic communication not only improves the santri's understanding of the yellowclassical books, but also strengthens their character and morality. This study concludes that Islamic communication is an essential element that supports the effectiveness of learning methods in salaf pesantren and contributes to the formation of a conducive and religious educational environment.